EFFECT OF HEALTH TEACHING ON KNOWLEDGE REGARDING SELF- CARE PRACTICES AMONG HYPOTHYROIDISM PATIENTS ADMITTED IN SELECTED HOSPITALS. - Mrs. Jayabala Aghamkar, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2024)
Hypothyroidism is a chronic endocrine condition characterized by deficient production of thyroid hormones, affecting physical and mental health. Effective management requires patient education on self-care practices. This study investigates the effect of health teaching on knowledge regarding self-care practices among hypothyroidism patients admitted to selected hospitals. A pre-experimental one-group pretest-posttest design was used, involving 30 patients selected via purposive sampling. Structured questionnaires assessed knowledge before and after health teaching interventions. Results showed significant improvement in knowledge, with 76.7% of participants achieving good knowledge in the posttest compared to 13.3% in the pretest. This study demonstrates the efficacy of health teaching in enhancing patient understanding of self-care practices, emphasizing its integration into routine clinical management of hypothyroidism.